2014
DOI: 10.1016/j.proeng.2014.12.206
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Compression Applied during Production to the Compression Strength of Dry Concrete: An Experimental Study

Abstract: Dry concrete is a cementitious material, consisting of aggregates imbedded in a cement matrix. The water cement factor is customary kept low, the compression stress is given to reduce the air voids in the mixture, to enable the entrapped water to optimize the hydration process, and to create more dense material so it will provide a better performance. This study uses 2 types of mix designs and 9 types of compressive stress. The experimental test showed that the greater compressive stress given duri ng the prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…SULISTYANA et al [20] avaliaram 9 graus distintos de compactação na obtenção de concretos secos. Identificaram uma relação direta entre a intensidade de compactação e a resistência do material, de tal forma que, quanto maior a pressão aplicada, maior a resistência obtida.…”
Section: Particularidades Do Concreto Secounclassified
“…SULISTYANA et al [20] avaliaram 9 graus distintos de compactação na obtenção de concretos secos. Identificaram uma relação direta entre a intensidade de compactação e a resistência do material, de tal forma que, quanto maior a pressão aplicada, maior a resistência obtida.…”
Section: Particularidades Do Concreto Secounclassified
“…The maximum compressive strength test results are around 70 Mpa or two times greater than the pressure without vibration when making test specimens. The following is a reverse study conducted by Arslan, ME (2011) with a mixture of high-quality concrete designs, using several types of b / c ratios between 0.3 to 0.6 and a time vibrating of 0 to 240 seconds without pressing, it found that compressive strength the maximum occurs between 65 seconds with an aw / c ratio of 0.3 [3]. The two studies above cannot be applied to the CPB manufacturing process except for low w/c, because the CPB manufacturing process demanded with fast processing and high compressive strength.…”
Section: Introductionmentioning
confidence: 98%
“…Layered concrete has many advantages, such as: saving construction time; saving overall cost; reducing cement consumption; having a high strength to overall weight ratio; and having good impact; thermal, and durability properties [17][18][19][20][21]. Utilizing alternative binders to replace cement in graded concrete with using lightweight concrete to reduce the overall weight can preserve the cement consumption and reduce the construction cost up to 50% [22][23][24][25][26]. Using normal strength concrete for satisfying required ductility in the compression zone and lightweight concrete for reducing overall weight in the tensile zone of the layered element shows good results, and no bond problems between concrete layers have been investigated [27].…”
Section: Introductionmentioning
confidence: 99%